The Development of Integrated Biology-Entrepreneurship Learning Design Based STEAM - Retnowati, Linda; Sugianto, Sugianto; Alimah, Siti (Journal of Innovative Science Education)
Biology learning design development is an important matter for teachers to be prepared. It is for the sake of realizing the 21st education for the learners. Learning biology also involves the technology role and its implications to obtain innovative and beneficial products for broader people. This research aims to examine the validity and effectiveness of the development of integrated biology-entrepreneurship based on STEAM learning design on a material about the environmental changes to improve critical thinking skills and the entrepreneurial interest of the learners. The applied development procedures were ADDIE model. The developed learning design consisted of syllabus, lesson plan, learning source, worksheet, critical thinking test, and entrepreneurial interest. The findings showed that (1) the validity of the learning was deemed valid and practical by the expert judgment; (2) the effectiveness of the learning design was proven able to improve the learners’ critical thinking skills with a percentage of 84%, with a sufficient N-Gain category and high category of entrepreneurial interest average improvement with a score of 77. The paired sample t-Test shows that tcount > ttable. Thus, it could be concluded that there was a significant difference between the critical thinking skills and the entrepreneurial interest. Based on the findings, it could be concluded that the biology learning with a material about the environmental changes integrated by entrepreneurship based on STEAM had highly met the validity criteria. It could improve the critical thinking skill and the entrepreneurial interest of the learners.